Falta de normativa en Ecuador para garantizar el derecho a tener una familia a las parejas heterosexuales que padecen esterilidad e infertilidad. - Eras Jaramillo, Ana Belén (2024)
The present work of Curricular Integration addresses the surrogate pregnancy, an assisted reproduction technique that allows heterosexual couples with infertility and sterility problems to have children. In Ecuador, the lack of policies regulating this practice generates significant legal and social conflicts. This research focuses on the need to regulate surrogacy in order to guarantee the right of these couples to form a family, by carrying out a comparative study, which also examines legislation in other countries that addresses this practice. Usually, one of the main goals that couples have is to have children and start a family. Throughout history and in various cultures, procreation has been seen as one of the essential functions of marriage and relationships. However, when couples face infertility and sterility problems, this can affect the relationship, living together, emotional well-being, creating conflicts that can end in separation and divorce. For the relevant development of this work, several research parameters have been established such as legal, conceptual and doctrinal, additionally, various methods were used: scientific, inductive, deductive, analytical, synthetic, exegetical, maieutic, comparative, and statistical. Regarding the fieldwork, techniques such as surveys and interviews were applied, from which the opinions of professionals were obtained in order to confirm the stated problem. After the legal and doctrinal study in the context of comparative law, it was determined that countries allowing surrogacy have clear regulations to ensure a safe process and the rights of those involved in this process. In addition, it was determined that the purpose of surrogacy is to help couples who cannot conceive to have genetically related children, giving them the chance to have a family. It was also found that in Ecuador this practice has been in place for many years and is regularly used by couples who cannot have children due to infertility problems; however, 5 no law has been established for its regulation, which means that it is carried out clandestinely and creates problems in the future. We conclude that the lack of legislation in Ecuador to regulate surrogacy leads to handle this issue from underground, putting at risk the rights of the parties. Therefore, it is important to implement a regulation that allows this practice in a safe and transparent way to avoid the violation of the rights of those involved in this process.